2016
DOI: 10.1080/01612840.2016.1208692
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Depression, and Self-Care Activities in Adult Jordanians with Type 2 Diabetes: The Role of Illness Perception

Abstract: Diabetes mellitus is reaching epidemic levels worldwide. In a developing country like Jordan, type 2 diabetes mellitus (T2DM) has reached a prevalence rate of 17.1%. This cross-sectional study examined the relationship between self-care activities and: illness perception, depression, social support, religiosity and spiritual coping, and self-efficacy among patients with T2DM. A random sample of 220 patients with T2DM, who attended Jordan University Hospital in Jordan were enrolled. The data were collected thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 48 publications
8
41
1
6
Order By: Relevance
“…The results in the final model further confirmed that self‐efficacy was a strong predictor of DSM behaviors. This is consistent with the results of numerous prior investigations (Al‐Amer et al., ; Bhandari & Kim, ; Cosansu & Erdogan, ; Devarajooh & Chinna, ; Gao et al., ; Hu, Dong et al., ; Kav et al., ; Ku & Kegels, ; Lin et al., ; Walker et al., ; Yang et al., ; Yuan et al., ; Yue et al., ; Zhao et al., ; Zhong et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results in the final model further confirmed that self‐efficacy was a strong predictor of DSM behaviors. This is consistent with the results of numerous prior investigations (Al‐Amer et al., ; Bhandari & Kim, ; Cosansu & Erdogan, ; Devarajooh & Chinna, ; Gao et al., ; Hu, Dong et al., ; Kav et al., ; Ku & Kegels, ; Lin et al., ; Walker et al., ; Yang et al., ; Yuan et al., ; Yue et al., ; Zhao et al., ; Zhong et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Self‐efficacy, which refers to the belief in one's capability to perform specific behaviors, plays a central role in the change of individuals’ behavior (Bandura, ). Cross‐sectional studies suggest that higher self‐efficacy is also associated with better DSM behaviors (Al‐Amer, Ramjan, Glew, Randall, & Salamonson, ; Bhandari & Kim, ; Cosansu & Erdogan, ; Devarajooh & Chinna, ; Gao et al., ; Hu, Dong, Wei, & Huang, ; Kav, Yilmaz, Bulut, & Dogan, ; Ku & Kegels, ; Lin et al., ; Walker, Gebregziabher, Martin‐Harris, & Egede, ; Yang et al., ; Yuan, Sun, Yu, Zhao, & Dong, ; Yue, Chen, Wang, Su, & Wu, ; Zhao et al., ; Zhong, Wang, Zhang, Ji, & Wang, ). Social cognitive theory also suggests that sources of information can influence behavior by affecting self‐efficacy, emotional status can affect the judgment of individuals’ self‐efficacy, and personal characteristics might have an impact on self‐efficacy (Bandura, ).…”
Section: Background and Significancementioning
confidence: 99%
“…Ten included studies evaluated foot care among diabetes patients from which two studies investigated foot care only (Shown in Table ). Six studies (Al‐Amer et al, ; Ashur et al, ; Assah et al, ; Bhandari & Kim, ; Mogre, Abanga, et al, ; Mosha & Rashidi, ) reported foot care adherence according to the mean number of days diabetes patients adhered to foot care recommendations; mean days ranged from 2.2–4.3 days in a week. Huang et al () reported a mean foot care practice score of 77.47% among Chinese persons with diabetes (higher scores indicate better self‐perceived overall foot care).…”
Section: Resultsmentioning
confidence: 99%
“…The validity and reliability were performed by Al-Amer et.al (2016) in Jordan and were taken into consideration. The DSES was translated into Arabic, with the Cronbach's alpha of the revised scale was 0.81 [22].…”
Section: Study Instrumentsmentioning
confidence: 99%